Nursing Leadership - Dias, Carlos Manuel de Melo (2004)
The senior nursing officer is the key-element in group work dynamics as the leadership manager for organisational efficiency in hospital ward practice nursing. Fiedler's Contingency Theory defines Leadership as a relationship in which power and influence are unevenly distributed, and whose efficiency depends on the contingency of the situation. The main subject of this paper consists in showing the result of assessment senior nursing officer leadership style that allows group work effectiveness. This study, had applied a quantitative research approach, of a descriptive-analytic type, to data provided by questionnaires with anonymous answers given by nurses working in hospital wards. Four different scales of Fred FIEDLER et al. (1976) were used: Least Preferred Co-Worker (leader's description of the least preferred co-worker), Relationship between Leader and Members (relationship's quality), Task Structure (task organisation and planning) and Power Position (leader's power over his/her subordinates). From the data analysed we could conclude that the senior nursing officer perceives leadership as relationship orientated, whereas the leadership situation control is classified as high, which according to the Contingency Theory indicates group work inefficient performance. Therefore, this study acknowledges that the senior nursing officer's function in hospital ward practice is in value crisis, needing for clarification from the health organisations and other nursing professionals. In conclusion, in order to find a solution for the current ineffective leadership practices of senior nursing officers, we suggest the adoption of the management measures recommended by Fiedler: leadership recruitment and selection, leadership training, and organisational engineering.